Draft Genome Sequence of Pseudoalteromonas luteoviolacea Strain B (ATCC 29581) - Cress, Brady F. (American Society for Microbiology, 2013)
We report the 4.049-Mbp high-quality draft assembly of the Pseudoalteromonas luteoviolacea strain B (ATCC 29581) genome. This marine species is known to biosynthesize several antimicrobial compounds, including the purple pigment violacein. Whole-genome sequencing and genome mining will complement experimental studies aimed at elucidating novel biosynthetic pathways capable of producing pharmaceutically relevant molecules. Based upon 16S rRNA phylogenetic analysis, we propose that strain ATCC 29581 be classified as a distinct phylogenetic species of the genus Pseudoalteromonas.